2022
DOI: 10.3390/jcm11133684
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health and Social Support Are Key Predictors of Resilience in German Women with Endometriosis during the COVID-19 Pandemic

Abstract: Background: Endometriosis is a multifaceted chronic pain disorder that can have an impact on both physical and mental health. Women suffering from chronic pain may be more susceptible to various health disorders, especially during adversity, such as the COVID-19 pandemic. Previous research has identified resilience as a mediator between internal or external stressors and well-being. Methods: An online survey was conducted during the first wave of the COVID-19 pandemic in Germany through patient support groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…For instance, a cross-sectional study of 408 young women reported menstrual pain in 84% of participants with more than half reporting the occurrence of pain during each period [4]. Thus, dysmenorrhea is one of the most common causes of pelvic pain and has an adverse impact on quality of life, work productivity, absenteeism, and health care utilization [1][2][3]5,6].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a cross-sectional study of 408 young women reported menstrual pain in 84% of participants with more than half reporting the occurrence of pain during each period [4]. Thus, dysmenorrhea is one of the most common causes of pelvic pain and has an adverse impact on quality of life, work productivity, absenteeism, and health care utilization [1][2][3]5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Of these, three published papers appear J.I. Spencer 1,2 , G. MezquIta 1 , F. ShakIr 1 to have analysed results from the same survey (Schwab et al,2021;Schwab et al, 2022a;Schwab et al,2022b). One mid-2020 case-control study in 1,027 patients in Iran showed no change in Covid-19 infection in endometriosis patients (Moazzami et al, 2021), whilst another smaller case-control study of 401 patients in Italy conducted between March 2020 and April 2021 showed a slight increase in number of infections in endometriosis patients (Barretta et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…There are only 14 published studies examining the effects of Covid-19 on endometriosis patients ( Arena et al, 2021 ; Armour et al, 2022 ; Ashkenazi et al, 2022 ; Barretta et al, 2022 ; Demetriou et al, 2021 ; Evans et al, 2021 ; Moazzami et al, 2021 ; Nicolás et al, 2022 ; Rosielle et al, 2021 ; Schwab et al, 2021 ; Schwab et al, 2022a ; Schwab et al, 2022b ; Uccella et al, 2021 ; Yalçın Bahat et al, 2020 ). Of these, three published papers appear to have analysed results from the same survey ( Schwab et al, 2021 ; Schwab et al, 2022a ; Schwab et al, 2022b ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations